FTIR microscopic image analysis based on 2DPCA - Xiu-kun YANG; Ming-liang ZHONG; Xiao-jun JING; Jie ZHANG (Tongxin xuebao)
In order to improve the efficiency of spectral unmixing,a novel spectral unmixing method based on 2DPCA in the spectral direction was developed.With the proposed method,spectra can be unmixed directly using the original image matrices.Simulation experiments performed on FTIR microscopic images of a rabbit artery and a multilayer paint chip verify the feasibility and effectiveness of the proposed algorithm.Experimental results demonstrate that when the FTIR microscopic image contains more spectra than spectral channels,the proposed algorithm has higher computation effi-ciency than PCA algorithm for spectral unmixing.Further more,the advantage of using 2DPCA becomes more obvious with an increase in the ratio of the number of spectra to the number of spectral channels.